A COVID-19 outbreak with a high attack rate among inpatients in a psychiatric hospital in Wenzhou, China - Zhou, Yiwei; Lin, Xingbao; Huang, Yu; Wu, Chunhua; Li, Jun; Huang, Jieru; Zhou, Zumu (German Medical Science GMS Publishing House, 2024)
Background: Since the emergence of COVID-19, China has taken strict prevention and control measures against the disease. At the end of 2022, when the government optimized and relaxed the COVID-19 prevention and control policy, a new wave of the epidemic appeared. This paper reports an outbreak of COVID-19 among inpatients in a psychiatric hospital in Wenzhou, China.Methods: The case definition of COVID-19 was established. Throat swab specimens were collected and examined by RT-PCT. Questionnaires were distributed to hospitalized patients. Survey data were collected and analyzed.Results: Of 902 inpatients in our hospital, 762 became infected with COVID-19, an attack rate of 84.5%. The outbreak occurred from 1ecember, 2022 to January 18, 2023. Twenty patients died, yielding a case fatality rate of 2.6%. Most of the dead were among elderly people with underlying diseases, and 19 of the deceased were over 65 years old. Conclusion: Our investigation showed that the outbreak of COVID-19 among hospitalized patients had the characteristics of high incidence, strong infectivity, and rapid transmission. Infectious sources were introduced into the hospital from the community and spread within the hospital, resulting in an outbreak. In addition, special attention should be paid to elderly people with underlying diseases when treating patients with COVID-19 in the future.